PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM DENGAN TINGKAT SUKU BUNGA SEBAGAI VARIABEL MODERASI PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sumitro; Giriati (Institut Shanti Bhuana, Program Studi Kewirausahaan, 2024)
Abstrak This study aims to analyze the influence of financial performance on stock returns of commercial banks listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, with interest rates as a moderating variable. Financial performance is measured using Return on Assets (ROA), Loan to Deposit Ratio (LDR), and Non-Performing Loan (NPL). The data utilized are quantitative, sourced from corporate financial reports and relevant macroeconomic data. The analysis was conducted using statistical methods with moderation regression testing. The results indicate that ROA and LDR have a significant positive impact on stock returns, while NPL has a significant negative impact. Interest rates were found to moderate the relationship between these variables and stock returns. Specifically, higher interest rates weaken the positive relationship between ROA and LDR with stock returns and exacerbate the negative effect of NPL on stock returns. This study provides practical implications for investors in making investment decisions and for bank management in managing financial performance and risk. Keywords: financial performance, stock returns, interest rates, ROA, LDR, NPL